The Transformative Role of Music in Visual Arts Education: Rediscovering Intercultural and Interdisciplinary Possibilities through A/r/tographic Inquiry - Ayşe GÜLER (Anı Publishing, 2021)
A/r/tographic inquiry is an art-based research method widely used abroad; this method has not yet become widespread in our country's undergraduate and graduate arts education. To reinvent the results of my a/r/tographic work, which I conducted by visualising the electroacoustic work "Symbolic Gestures" by Malaysian composer and academician Valerie Ross in 2017, with this study I invite my students to an a/r/tographic investigation (understanding/interpretation with artist identity). I aim to reveal intercultural and interdisciplinary creative learning experiences for my students with the methods and techniques (theorising/theory with researcher identity) that I discovered while questioning the transformative role of music in my creative process, and re-question my teaching and learning identities (practice with a teacher identity) through artistic practices. This study reveals a 6-week intercultural and interdisciplinary a/r/tographic inquiry in 2018-2019 with 12 undergraduate and 4 graduate students studying research and art. The research data consists of video and audio recordings, photographs, artistic products, student views, observation notes, diaries, and the work named Symbolic Gestures. The data were interpreted with an a/r/tographic inquiry approach. At the end of the research, the transformative role of music in visual arts education has produced significant results in the experiences of knowing, creating, metaphorical thinking, intuitive listening, and seeing in depth in undergraduate and graduate art students. The provocative, transformative, and convertible role of music can be used in learning, creating, and teaching experiences in visual arts education.